The Role of the Private Sector in Providing Basic Education Services in Kasoa, Ghana - Abdul-Hamid, Husein (World Bank, Washington, DC, 2017)
Despite significant government investments in the public education system, population growth and migration have led to an undersupply of school places, especially in urban centers, leading to an increase in private education enrollments in Ghana. Ghana has nearly doubled enrollment at the primary and junior high school levels since the introduction of free and compulsory universal basic education. Ghana’s primary net enrollment rate of 86.8 percent in 2013 is still slightly below the average for lower-middle-income countries, which was 87.3 percent. Its net rate of secondary enrollment (including junior and senior high school), 51 percent, is also lower than the 58 percent average for lower-middle-income countries (EdStats). Ghana’s public spending on education is comparable to that of other middle-income countries and the government is currently focusing its attention on upper secondary education (senior high school), with plans to build more schools to increase access. Rising enrollment rates have not been accompanied by gains in student learning; some parents are choosing private schools due to their perceived higher quality. The education system in Ghana is currently facing fiscal pressures due to low levels of accountability, inefficient allocation of resources, and plans to expand upper secondary provision. Although the Ghanaian government has made progress in improving equitable access to education through new programs and policies, government resources are currently unevenly distributed across regions in terms of spending per pupil as well as the allocation of teachers. Ghana currently has a budget deficit, with teacher salaries forming a large part of recurrent costs in education. The country also plans to expand education at the senior secondary level to meet the needs of the economy. The construction of 200 schools will put further pressure on government budgets.